Seismiflex joint system for precast concrete wall panel - Fuad, Umairah; Ismail, Asmat (2024)
In Malaysia, the widespread use of Industrialized Building Systems (IBS), particularly precast construction, is prevalent. However, the country faces a growing concern regarding seismic events, as recent minor earthquakes have caused slight structural damage. This highlights the need for early preventive measures, especially as seismic activities appear to be increasing. This study aims to maximize earthquake resistance during seismic events to prevent post-earthquake damage to the low-rise building. The research methodology includes comprehensive document reviews, iterative idea generation sessions, and sophisticated 3D simulation modelling using Sketchup software with findings expected to offer practical recommendations for application. The predicted outcomes include advancements in the understanding of seismic resilience in low-rise construction. Ethical considerations guide the process of the research, ensuring integrity and confidentiality. This research seeks to innovate and elevate the standards of seismic resistance in precast concrete construction, potentially offering commercial applications for enhanced building safety.